Mobilisasi Dini Post Sectio Caesarea Dengan Proses Penyembuhan Luka Operasi Di Rs Anutapura Palu - Ni Made Rosiyana; H. Saleh muliadi; Emerentiana Niluh, Angela (Akademi Kebidanan Palu Sulawesi Tengah, 2020)
In order to help the path of wound healing, mothers after cesarean section are advised to do early mobilization. The purpose of conducting the study was to analyze whether there was a relationship between early mobilization of post-sectio caesarean mothers with the wound healing process. The research method used was analytic with a cross sectional study approach. This research was conducted at Anutapura Hospital, Palu on July 2-July 18 2020 with a total sample of 22 respondents. Based on the chi-square test, the results of Asymp Sig (2-sided) are greater than alpha 0.05 (0.350 > 0.05). Ha is rejected and Ho is accepted. These results indicate that there is no relationship between Early Mobilization of Post Sectio Caesarea and the process of healing surgical wounds at Anutapura Hospital, Palu, 10 (45.5%) who mobilized well with good wound healing and found that early mobilization was not successful. good there were 11 (50.0%) with good wound healing and 1 (4.5%) with poor wound healing. Based on the results of the study, it can be concluded that there is no relationship between early mobilization of post-caesarean section with the healing process of surgical wounds.